Modeling the Black Hole Recoil from the Nucleus - Ferrari, Guilherme (2013)
GEMINI + GMOS and Chandra emission-line spectroscopy reveal that the Fanaroff-Riley II radio-source J133658.3- 295105 is a local object behind the barred-spiral galaxy M83 that is projected onto the galaxy?s disk at about 60" from the galaxy?s optical nucleus. J133658.3-295105 and its radiolobes are aligned with the optical nucleus of M83 and two other radio-sources neither of which are supernova remnants or HII regions. The optical nucleus of M83 is off-centered by 2.7" (~60 pc) with regard to the kinematic center. Its mass is within the range (1 - 4) × 106 Msun and the velocity dispersion at its center points to a non-resolved mass concentration of <~106 Msun. In this paper we study the circumstances in which the radio source would have been ejected from the central region of M83. We analyze different types of collisions of binary and triple systems of super-massive black holes (SMBHs) by numerical simulations using a Post-New- tonian approximation of order 7/2 (~1/c7). We developed an N-body code specially built to numerically integrate the Post-Newtonian equations of motion with a symplectic method. Numerical experiments show that the code is robust enough to handle virtually any mass ratio between particles and to follow the interaction up to a SMBH separation of three Schwarzschild radii. We show that within the current Post-Newtonian approximation, a scenario in which one of the three SMBHs suffers a slingshot-like kick is best suited to explain the ejection of J133658.3-295105, which simultaneously produces the recoil of the remaining BH pair, which drags together a subset of stars from the original cluster forming a structure that mimics the offcenter optical nucleus of M83. The simulation parameters are tuned to reproduce the velocities and positions of J133658.3-295105 as well as the optical nucleus and the putative SMBH at its center.